Characteristics and Outcomes of ERCP at a Canadian Tertiary Centre: Initial Results from a Prospective High-Fidelity Biliary Endoscopy Registry. Issue 2 (28th February 2020) - Forbes, Nauzer; Koury, Hannah F; Bass, Sydney; Cole, Martin; Mohamed, Rachid; Turbide, Christian; Gonzalez-Moreno, Emmanuel; Kayal, Ahmed; Chau, Millie; Lethebe, B Cord; Hilsden, Robert J; Heitman, Steven J
Abstract: Background: Endoscopic retrograde cholangiopancreatography (ERCP) is an essential procedure in the management of pancreatic and biliary disease. While its role is firmly established, further well-designed prospective ERCP research is required, as a large portion of previous work has employed retrospective or administrative methodologies, both prone to potential biases. The aim of the Calgary Registry for Advanced and Therapeutic Endoscopy (CReATE) is to be a high-fidelity prospective multicentre registry. Methods: The study population consisted of consecutive adult ERCP patients from September 2018 to September 2019. Informed consent was acquired for each patient. All relevant preprocedural, procedural, peri-procedural and postprocedural data were captured in real time by a full-time third-party research assistant directly observing procedures. Outcomes were ascertained by comprehensive medical record review and patient phone interview 30 days after the index procedure. Results: Five endoscopists performed 895 ERCP procedures, 90.1% of which were deemed successful. Suspected choledocholithiasis was the most common indication for ERCP, followed by suspected or confirmed stricture(s), at 61.0% and 29.5%, respectively. 61.0% of procedures were performed on ERCP-naive patients. Post-ERCP pancreatitis occurred following 4.9% of procedures, with clinically significant bleeding or perforation occurring following 1.8% and 0.1% of procedures, respectively. Discussion: Through 12 months, CReATE captured 895 procedures prospectively, with each entry containing over 300 data fields. Active expansion to additional tertiary centres is underway, and this will enhance the existing data pool. CReATE has the potential to improve multiple facets of ERCP, including training, optimal procedural techniques, mitigation of adverse events and personalized patient care.